Dietary Intake According to the Course of Symptoms of Eating Disorders in a School‐based Follow‐up Study of Adolescents. (26th August 2014) - Aparicio‐Llopis, Estefania; Canals, Josefa; Arija, Victoria
Abstract This study examines dietary intake according to the course of risk of eating disorder (rED) in a sample of school‐age followed from preadolescence to adolescence. An initial sample of 1 336 adolescents completed the Children's Eating Attitudes Test, and we selected a group with rED and a control group randomly. Two years later, 162 adolescents completed the Eating Attitudes Test and were classified into three groups according to the course of symptoms (no rED = 57; remission of rED = 62; persistent rED = 43). Dietary intake was assessed using a 3‐day food record and 24‐h recalls over 3 days. The results showed that girls with persistent rED reduced their energy and nutrient intake, with a 67.5% at risk of inadequate vitamin and mineral intake. Boys with persistent rED maintained their dietary intake, with a 25% at risk of inadequate vitamin and mineral micronutrient intake. Therefore, early detection of rED is necessary to prevent the exacerbation of nutritional problems. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.